Historia Y MEMORIA: Almost 10 years consolidating a historiographic community. An overview from Bibliometry. - Gómez, Nubia Yanet; Acuña Rodríguez, Olga Yanet; Bautista, Andrés Felipe (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents an analysis of the journal HISTORIA Y MEMORIA as a means of communication and scientific publication in the area of social history, it's development and its insertion in the academic community in this field. The starting point is a reflection on the editorial trajectory in the field of social history in which memory is a substantial referent of analysis for historians because it allows for the understanding other problems, other actors, other scenarios, and, above all, other sources; all this, in order to understand the voices of the invisible, the marginalised and other groups that have remained anonymous. This reflection is based on a bibliometric analysis in which themes, authors, as well as the connection and origin of the authors is evaluated, until the point of understanding how the journal, in its 9 years of existence, has managed to position itself in the field of historical knowledge in Colombia and in an international context.